Activating spatial inequality: the case of the UK Work Programme. (1st June 2020) - Whitworth, Adam
Abstract : International evidence finds consistent equity concerns in quasi-marketised activation policies in terms of systematically worse experiences and outcomes for service users with greater support needs. However, equivalent risks around spatial inequalities are neglected within policy debates and empirical analyses. This article responds to that ongoing geographical gap through rich spatial analysis of the UK's Work Programme, a vanguard experiment in aggressively quasi-marketised employment activation policy. Findings show consistent evidence for spatial inequalities in outcomes patterned according to local economic deprivation, with more deprived local authorities losing out on millions of pounds compared to the per capita resourcing in wealthier areas.